Evaluación de cultivares comerciales de garbanzo frente a Ascochyta rabiei en Argentina - Pastor, Silvina Estela; Crociara, Clara Sonia; Valetti, Lucio; Pugliese, Bruno Daniel; Fekete, Ana Cecilia (Asociación Argentina de Fitopatólogos, 2022)
Poster